PENGEMBANGAN ALAT EVALUASI BERBASIS QUIZIZZ TEMA I INDAHNYA KEBERSAMAAN SUB TEMA I KEBERAGAMAN BUDAYA BANGSAKU UNTUK SISWA KELAS IV SEKOLAH DASAR - Indah Ningtyas, Dwi Lestari; Wiratsiwi, Wendri (Prosiding SNasPPM, 2021)
In order to realize the process of teaching and learning, then it is very necessary series of learning activities, evaluation of learning, including the learning process, the learning achievement as an indicator of an education. Learning can be an indicator of absorption of the intelligence of learners. In the process of learning, because the participants but that is expected to absorb all of the lesson material. The purpose of this study is to describe the validity, practicality evaluation tool using application quizizz. The type of this research is the development (research and development) by using the model of ADDIE. The Data is processed shaped descriptive quantitative. The quantitative Data obtained from the input of teachers and students of class IV SDN Foregoing 1 a number of 20 children. And qualitative data obtained from criticism and suggestions given by the validator and the user. The results of this study show the following: (1) the development of an evaluation tool through five stages, namely the stage of requirements analysis, design, development, implementation and evaluation. (2) based on the test of the validity of the material and the media showed the level of validity of the expert of the material by 90% with the category of very valid, media experts to 95% with the category of very valid. While (3) the level of practicality obtained from the questionnaire of teachers and students of class IV are of 88.1% included in the category of very valid. (4) the Level of effectiveness obtained from calculating the evaluation value of 20 students who obtain the classical completeness with a score of 75 evaluation tool based on quizizz is effective because the analysis of learners achieve the classical completeness. Keywords: Development, Evaluation Tool, Based quizizz